(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article presents an analysis of the current state of foreign economic relations between the Russian Federation and a number of Arab countries, as well as identifies key factors influencing their development. The features of bilateral trade cooperation between the Russian Federation and such Arab countries as Oman, Saudi Arabia and the United Arab Emirates are considered. The main directions of Russia’s foreign economic activity with the above-mentioned countries of the Persian Gulf have been identified.